Książki Barbary Gawryluk lekarstwem na problemy duszy - Katarzyna Kotaba (Paidia i Literatura, 2021)
This article is an attempt to examine whether literature can be a remedy for the problems faced by children of different ages. The report Children’s rights from the perspective of children, parents and teachers was published in 2019 by UNICEF Polska. It has been used to diagnose the reasons for unhappiness among children aged 12—17. Among the reasons are: school and education, relationships with loved ones, relationships with peers. In her article, Katarzyna Kotaba refers to such authorities as Irena Borecka, Maria Molicka, and Bruno Bettelheim and to their unanimous opinion that good and valuable literature takes seriously children, their concerns and difficulties; moreover, this kind of literature helps children to overcome difficulties by building their self-confidence. Kotaba identifies the main thematic motifs in Gawryluk’s fiction and shows how this writer’s novels can help under-age readers cope in specific life situations, such as the parents’ divorce, emigration, and racism. In conclusion, she suggests that Gawryluk’s novels could be regarded as a cure for young readers’ problems as identified in the UNICEF report.